Prospects for financialised water provision: going beyond public/private ownership debates - Teles, Nuno (2016)
In the last decades, water provision has undergone profound transformations. After the disappointing results of various privatisation experiences, both in developed and developing countries, a movement towards remunicipalisation of water provision took place. However, the return to the public domain of water systems has not entailed a retreat of private capital. Through the scrutiny of recent developments in Portugal, this paper argues that financialisation of the water sector has enabled a more pervasive and enduring participation of private capital, involving multiple institutional arrangements. This resulted in the increasing capture of income from household water bills by the financial sphere. A future scenario for the financialisation of water provision is presented, identifying the various new ways whereby finance may exert an ever growing influence over the sector.